Stability and optimal measures analysis on the transmission dynamics of Tuberculosis by means of fractional order - Loyinmi, Adedapo (Covenant Journal of Physical and Life Sciences, 2025)
While being a treatable and preventable disease, tuberculosis (TB) nonetheless poses a serious global health threat and claims millions of lives each year. In this study, a sophisticated mathematical technique from fractional calculus theory is used to explore the complex dynamics of tuberculosis transmission. To capture the subtle progression of tuberculosis infection, the study employs an SEIR model that categorizes the population into distinct compartments. The potential of fractional calculus to transform epidemiological research by simulating the dynamics of infectious diseases was demonstrated through its use. By leveraging the intrinsic flexibility and precision of fractional derivatives, we enhance our understanding of tuberculosis epidemiology and establish the foundation for innovative methods in disease control and prevention. The intricate interactions between susceptible, vaccinated, latent, treated, acute, and recovered individuals in the population were discussed using careful analysis and numerical simulations. The efficiency of several control tactics, including vaccination, treatment of latent and current cases and preventive measures is clarified by key findings from the study. How these interventions affect the dynamics of tuberculosis transmission, community immunity, and disease burden was clarified. In addition, the study provides important information for public health practitioners and policymakers highlighting the varying effectiveness of control methods in reducing transmission and increasing recovery rates. Also, the study is a step forward in epidemiology, providing a comprehensive understanding of the dynamics of TB transmission and the effectiveness of control measures using fractional derivatives. The results of this study are expected to be a guide for evidence-based initiatives, ultimately buttressing international efforts to fight tuberculosis and enhance public health.